Research Regarding the Effects of Ultra-highly Insulated Homes in Regions with Great External Thermal Load in Summer on Energy Conservation - Hama Y; Fukuda H (Bandar Lampung University (UBL), 2017)
It is being conducted by Haraguchi et al.1) that study of ultra-high insulation housing that combination of Air circulation type whole building air conditioning system and Passive active heating method. In the studied houses of 6 buildings on 6 regions with different climatic characteristics were verified by simulation has been performed. There is effective in reducing cooling and heating load in each studied houses of each area. However, the model of studied house built in Miyazaki city that is the warmest region of the six regions is the air conditioning load reduction rate is smaller than the model in other areas. This study actually measures and simulates how much energy-saving effect can be demonstrated ultrahigh insulation houses in areas with high external heat load during the summer. During the winter, even after the air conditioner has stopped, LDK temperature is less likely to decrease compared to the outside temperature. In the daytime, room temperature rises without air conditioning by heat in double skin and heat acquisition by solar radiation. During the summer, despite the whole air conditioning depends on one air conditioner, very stable room temperature is maintained. Regions where the external thermal load of the summer season is larger than that of Miyazaki City like a Naha city also annual air-conditioning load is reduced as heat insulation performance improves